"A Little Bit Christian": Memories of Conversion and Community in Post‐Christian Amazonia. Issue 2 (23rd May 2016) - High, Casey
ABSTRACT: Conversion to Christianity in Amazonia is often described in terms of collective action rather than radically new beliefs interior to the individual. I describe how Waorani people in Ecuador remember the conversion of specific elders as a time of civilization that brought Waorani into a wider social order after a period of violence and isolation. Despite having largely abandoned Christianity since their mass conversion in the 1960s, Waorani today embrace past conversion as a catalyst of social transformation that they say made the present ideal of living in a "community" possible. The individual experiences evoked in memories of collective "civilization" and an insistence on personal autonomy in Waorani visions of community illustrate why the moral commentaries of Waorani Christians remain highly valued in communities where Christianity has ceased to be a dominant social identity. [ conversion to Christianity, memory, temporality, Amazonian personhood, community, Waorani ]